Hidden Aggression in Adolescence – What Do Teachers Need to Know? - Sevdzhihan Eyubova (ARPHA Proceedings, 2019)
Aggression is one of the most frequently researched topics by a wide range of specialists - psychologists, teachers, sociologists, medical specialists and others at that. Reports on the increase in the frequency of aggressive behaviors are not new, which over time also outlines the tendency to reduce the age of severe aggressive acts and to perceive the aggressive response as the norm for resolving different conflicts. The indifference and the lack of sensitivity to aggression by others become even more disturbing. This leads to changes in the direction of aggression - data from international empirical studies over the past twenty years show a very high frequency of self-aggression during adolescence. This report presents the results of a first of its kind study of the display of hidden aggression and self-harm in teenage pupils from Bulgaria. 454 adolescents, aged 13 to 19, students from 7 to 12 grade from a profiled high school in Shumen are subject to research. The study was conducted on the territory of the school, after informing the Regional Educational Administration and receiving written informed consent from the pupils’ parents. For the purpose of the study, a special methodological tool, ISAS - Inventory of Statements on Self-Injury (Klonsky & Glenn, 2009) was selected. ISAS is a questionnaire consisting of two parts - behavioral and functional, with good psychometric characteristics. The first part of the questionnaire gathers information about whether the subjects injure themselves, the type of the self-injury and the frequency of auto-aggressive behaviors; the second, "functional" part, assesses different functions of self-harming behaviors. The use of ISAS allowed the differentiation of a group of individuals who self-harm from the total number of students (n = 454) - 163 students reported self-inflicted injuries, 58% of them being girls and 42% boys. Factor analysis of the results supported the assumption that auto-aggressive behaviors in adolescence serve primarily to regulate emotions. Over 2/3 (83%) of the adolescents surveyed reported having physical pain and nearly half (46%) were not alone when self-injuring, which is indicative of the fact that these behaviors also serve as a form of communication with others, which must be taken into account due to its destructive and risky nature. Adolescence is one of the most vulnerable periods in life, and adolescents need the support of parents, teachers, peers, consultants, and medical professionals. Self-harm, which is a form of cloaked aggression directed at the personality itself, is seen as a predictor and a risk factor for the most extreme and fatal form of auto-aggression among adolescents - the suicide. The results of the study can be of benefit to all specialists involved in studying adolescent aggression and self-aggression, but also to the planning of evidence-based preventive and therapeutic programs.